Inorganic grouting material for in-situ reinforcement and repair of external wall thermal insulation layer and preparation method of inorganic grouting material
By using inorganic grouting material and microwave foaming technology, the problems of disturbing the public, not environmentally friendly and poor repair results in the repair process of the exterior wall insulation layer in the existing technology have been solved, and an efficient, safe and environmentally friendly in-situ reinforcement and repair of the exterior wall insulation layer is achieved.
Patent Information
- Application Number
- CN202510099501.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art has problems such as disturbing the public, not environmentally friendly, complicated processes and long repair cycles when repairing the exterior wall insulation layer. The grouting materials have fast foaming speed and poor fluidity, making them difficult to fully fill the gaps, and organic grouting materials may affect fire resistance.
Inorganic grouting material is used, mainly made of vacuum aluminum thermal reduction lithium slag powder, siliceous blend, foaming material, active exciter, viscosity improver, foam stabilizer, surfactant and water, and release CO2 gas by microwave irradiation of the foaming material to fully fill the gap between the insulation layer and the base wall.
It realizes the high bonding strength and good insulation performance of inorganic grouting materials, and can quickly, safely and environmentally friendly reinforcement and repair the exterior wall insulation layer, reducing environmental pollution and improving the repair effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste recycling and reuse, and specifically relates to an inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer and a preparation method thereof. Background Art
[0002] At present, many cities in China have gradually entered the era of existing housing, among which some existing building envelope systems have reached 60% to 80% of their design service life. Under the influence of natural environment or human damage, the exterior walls of buildings are constantly degrading with the extension of service age. Various problems such as cracking and falling of exterior wall panels, cracks in corners, water seepage, water leakage in doors and windows, and falling of insulation boards and wall tiles have occurred frequently, which has reduced the safety of houses, affected people's daily lives, and even endangered people's personal safety. It is necessary to repair the exterior walls of old houses.
[0003] The renewal and repair of the exterior wall system of existing buildings is a current research hotspot. Some achievements have been made in China in the treatment and repair of exterior wall cracks, leakage, hollowing and large-scale shedding. The main approach is to remove the system as a whole or in part and then replace it, and select materials, design and construct it according to new construction standards. This approach is mostly temporary and emergency repairs, which have the disadvantages of disturbing residents, being environmentally unfriendly, complicated procedures and long repair cycles. It is not only easy to cause many exterior walls to have quality problems such as cracking and hollowing after repair, but even fire accidents such as fire and falling may occur during the renewal process. At present, the market urgently needs a "safe, fast, environmentally friendly, non-disturbing and economically reasonable" exterior wall renewal system solution.
[0004] The commonly used grouting material is polyurethane grouting material, which has good bonding properties with various insulation layers, but its foaming speed is fast and its fluidity is poor, making it difficult to fully fill the gap between the insulation layer and the base wall, and the repair and reinforcement effect is difficult to predict. At the same time, as an organic grouting material, when it is applied to the exterior walls of buildings, it is easy to have a negative impact on the fire resistance of the exterior wall insulation layer. Summary of the invention
[0005] In view of the problems and shortcomings in the prior art, the object of the present invention is to provide an inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer and a preparation method thereof.
[0006] Based on the above purpose, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides an inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer. The inorganic grouting material is mainly made of the following raw materials in parts by weight: 24 to 56 parts of vacuum aluminothermic reduction lithium slag powder, 10 to 30 parts of siliceous admixture, 10 to 20 parts of foaming material, 2 to 5 parts of active stimulant, 2 to 4 parts of viscosity improver, 1 to 2 parts of foam stabilizer, 0.5 to 1.5 parts of surfactant, and 13.5 to 18.5 parts of water.
[0008] Preferably, the foaming material is prepared by the following method: one or more of waste rubber, waste asphalt waterproofing membrane, and waste plastic are carbonized into a porous carbon material and then immersed in an impregnation liquid, and then the impregnated porous carbon material is placed in a critical CO2 environment to fully adsorb CO2, thereby obtaining the foaming material; the impregnation liquid is one or more of ethanolamine, ethylenediamine, and tetraethylenepentamine.
[0009] Furthermore, the specific preparation steps of the foaming material are:
[0010] S1: directly carbonizing at least one of waste rubber, waste asphalt waterproofing membrane, and waste plastic into a porous carbon material by heating at 600° C. for 45 to 75 minutes under anaerobic conditions;
[0011] S2: crushing and sieving the porous carbon material prepared in S1 to prepare porous carbon particles with a particle size of no more than 0.5 mm;
[0012] S3: immersing the porous carbon particles prepared in S2 in a solution of at least one of ethanolamine, ethylenediamine, and tetraethylenepentamine for at least 72 hours to functionalize the amine groups, thereby preparing impregnated porous carbon particles;
[0013] S4: placing the impregnated porous carbon particles obtained in S3 in a critical CO2 environment to fully absorb CO2, thereby obtaining the foaming material.
[0014] Preferably, the vacuum aluminothermic reduction lithium slag powder is a reduction slag produced by reducing metallic lithium by a vacuum aluminothermic method, and the average particle size of the vacuum aluminothermic reduction lithium slag powder is not greater than 100 μm.
[0015] Preferably, the siliceous admixture is one or more of organic silicon waste residue, ultrafine fly ash, and silica ash, and the average particle size of the siliceous admixture is not greater than 10 μm.
[0016] Preferably, the activity stimulant is an alkaline solution, and the alkaline solution is at least one of NaOH, Na2CO3, Na2SiO3, and KOH.
[0017] Preferably, the viscosity modifier is at least one of bentonite, attapulgite and diatomaceous earth.
[0018] Preferably, the foam stabilizer is at least one of redispersible latex powder, hydroxypropyl methylcellulose and xanthan gum.
[0019] Preferably, the surfactant is a sodium salt of polycarboxylate.
[0020] The second aspect of the present invention provides a method for preparing the inorganic grouting material for in-situ reinforcement and repair of the exterior wall insulation layer as described in the first aspect, comprising the following steps:
[0021] S1: Add active stimulant, foam stabilizer and surfactant into water in sequence and mix evenly to obtain a mixed solution;
[0022] S2: mixing the vacuum aluminothermic reduction lithium slag powder, the siliceous admixture and the viscosity improver uniformly to obtain a mixture;
[0023] S3: adding the mixture obtained in S2 and the foaming material to the mixed solution obtained in S1 in sequence, and stirring evenly to obtain a slurry;
[0024] S4: When in use, the slurry obtained in S3 is injected into the part of the exterior wall insulation layer that needs to be repaired and reinforced, and then the repair part is irradiated with 1000MHz to 3000MHz microwaves for 5 to 8 minutes to obtain the inorganic grouting material for in-situ reinforcement and repair of the exterior wall insulation layer.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) As the process of preparing metallic lithium by vacuum aluminothermic reduction has gradually matured, the corresponding output of vacuum aluminothermic reduction lithium slag has gradually increased, causing certain environmental pollution. The present invention utilizes the potential gelling properties of vacuum aluminothermic reduction lithium slag, and uses the calcium and aluminum mineral components in the vacuum aluminothermic reduction lithium slag, combined with silicon admixtures, to react under the action of an active activator to obtain an inorganic gelling material with high bonding strength. At the same time, the vacuum aluminothermic reduction lithium slag is effectively reused to reduce environmental pollution.
[0027] (2) The present invention uses waste rubber, waste asphalt waterproofing membrane, waste plastic and other materials as carbon sources to prepare porous carbon materials, and then uses processes such as impregnation with amine solution and adsorption of critical CO2 to make it absorb a large amount of CO2 to prepare a foaming material. After grouting, the foaming material undergoes a desorption reaction under microwave irradiation, releasing CO2 gas, so that the grouting material foams, and can then fully fill the gap between the insulation layer and the base wall, thereby improving the reinforcement and repair effect.
[0028] (3) When the present invention adopts microwave irradiation foaming, the amount of grouting foaming can be controlled by controlling the microwave power and irradiation time, and the foaming position can be controlled, so as to achieve repair work for different parts. On the other hand, the CO2 gas released by the microwave irradiation foaming material can react with the inorganic gelling material prepared by vacuum aluminothermic reduction of lithium slag to carbonize, and quickly improve its bonding strength.
[0029] (4) The present invention adopts viscosity improvers and surfactants, which not only makes the grouting material easy to grout and reduces the drying shrinkage of the grouting material, but also can quickly increase the viscosity of the slurry after the flow rate is slowed down, improve the surface free energy of the gas-liquid interface, and form a large number of independent bubbles inside the slurry during foaming, further improving the thermal insulation performance.
[0030] (5) The inorganic grouting material obtained by the present invention for in-situ reinforcement and repair of the exterior wall insulation layer can be used for in-situ grouting of the exterior wall insulation layer, which can not only improve the repair effect, but also the main components are prepared from industrial solid waste, and have excellent fire retardant properties and ecological environmental benefits. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail by way of embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Preparation: Preparation of foaming materials
[0033] S1: The waste rubber was directly carbonized into porous carbon material by heating at 600 °C for 60 min under anaerobic conditions;
[0034] S2: crushing and sieving the porous carbon material obtained in S1 into porous carbon particles with a particle size not greater than 0.5 mm;
[0035] S3: The porous carbon particles prepared in S2 are immersed in an ethanolamine solution for 72 hours to functionalize the amine groups, thereby obtaining immersed porous carbon particles;
[0036] S4: placing the impregnated porous carbon particles obtained in S3 in a critical CO2 environment to allow them to fully absorb CO2, thereby obtaining a foaming material.
[0037] (I) Investigate the effect of vacuum aluminothermic reduction lithium slag powder and siliceous admixture dosage on the performance of inorganic grouting materials for in-situ reinforcement and repair
[0038] Example 1
[0039] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer is mainly made of the following raw materials in parts by weight: 43 parts of vacuum aluminothermic reduction lithium slag powder, 18 parts of siliceous admixture, 15 parts of foaming material, 2.5 parts of active activator, 2.5 parts of viscosity improver, 1.5 parts of foam stabilizer, 1 part of surfactant, and 16 parts of water.
[0040] The preparation method of the above-mentioned inorganic grouting material comprises the following steps:
[0041] S1: 2.5 parts by weight of an active stimulant (10% NaOH solution), 1.5 parts by weight of a foam stabilizer (redispersible latex powder), and 1 part by weight of a surfactant (sodium polycarboxylate) are sequentially added to 16 parts by weight of water and mixed evenly to obtain a mixed solution;
[0042] S2: 43 parts by weight of vacuum aluminothermic reduction lithium slag powder, 18 parts by weight of siliceous admixture (ultrafine fly ash), and 2.5 parts by weight of viscosity improver (bentonite) are uniformly mixed to obtain a mixture;
[0043] S3: adding the mixture obtained in S2 and 15 parts by weight of the foaming material to the mixed solution obtained in S1 in sequence, and stirring evenly to obtain a slurry;
[0044] S4: When in use, the slurry obtained in S3 is injected into the part of the external wall insulation layer that needs to be repaired and reinforced, and then the repaired part is irradiated with 2000 MHz microwaves for 6 minutes to obtain the inorganic grouting material for in-situ reinforcement and repair of the external wall insulation layer.
[0045] Example 2
[0046] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, whose components and preparation method are basically the same as those of Example 1, except that the amounts of vacuum aluminothermic reduction lithium slag powder and siliceous admixture (ultrafine fly ash) added in step S2 are 56 parts by weight and 10 parts by weight, respectively.
[0047] Example 3
[0048] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, whose components and preparation method are basically the same as those of Example 1, except that the amounts of vacuum aluminothermic reduction lithium slag powder and siliceous admixture (ultrafine fly ash) added in step S2 are 30 parts by weight and 24 parts by weight, respectively.
[0049] Comparative Example 1
[0050] An inorganic grouting material, whose components and preparation method are basically the same as those of Example 1, except that in step S2, no vacuum aluminothermic reduction lithium slag powder and siliceous admixture (ultrafine fly ash) are added, and their dosage is 0.
[0051] Performance test: The samples obtained in Examples 1 to 3 and Comparative Example 1 were tested for tensile bond strength with cement mortar, tensile bond strength with insulation board, and slip according to the method described in T / CECS 574-2019 "Technical Code for External Insulation Renovation of Exterior Walls of Existing Buildings"; and their density was tested according to the method described in GB / T 5486-2008 "Test Methods for Inorganic Hard Insulation Products". Since the amount of vacuum aluminothermic reduction lithium slag powder and siliceous admixture (ultrafine fly ash) in Comparative Example 1 is 0, that is, there is no cementitious material in the grouting material, it cannot be formed, and the corresponding items cannot be tested and verified. The test results are shown in Table 1.
[0052] Table 1 Performance test of different amounts of vacuum aluminothermic reduction lithium slag powder and silicon admixture in Examples 1 to 3 and Comparative Example 1
[0053]
[0054]
[0055] It can be seen from Table 1 that adjusting the amount of vacuum aluminothermic reduction lithium slag powder and ultrafine fly ash in Examples 1 to 3 has an impact on the tensile bond strength, slip and density of the grouting material. This is because the main components of vacuum aluminothermic reduction lithium slag powder are active calcium raw materials and active aluminum raw materials; the main components of ultrafine fly ash are active silicon raw materials. Both of them mainly act as cementitious materials in the grouting material. When the proportion of the three elements of calcium, silicon and aluminum is appropriate, its strength can be improved. As shown in Table 1, the grouting material in Example 1 has the highest strength; however, the vacuum aluminothermic reduction lithium slag powder in Example 2 is too much, and the ultrafine fly ash in Example 3 is too much, which changes the proportion of the three elements of calcium, silicon and aluminum in the grouting material, affecting the tensile bond strength of the grouting material.
[0056] On the other hand, in Example 2, the vacuum aluminothermic reduction lithium slag powder is relatively large, and its particle size is relatively large, and the proportion of water adsorbed on the surface of the particles in the grouting material decreases, which makes the slurry viscosity decrease, easier to foam, and increases the slippage and decreases the density. In contrast, in Example 3, there is more ultrafine fly ash with a relatively small particle size, which decreases the slippage and increases the density.
[0057] (II) Investigate the effect of foaming material dosage on the performance of inorganic grouting materials for in-situ reinforcement and repair
[0058] Example 4
[0059] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, wherein the components and preparation method thereof are substantially the same as those of Example 1, except that the amount of the foaming material added in step S3 is 10 parts by weight.
[0060] Example 5
[0061] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, wherein the components and preparation method thereof are substantially the same as those of Example 1, except that the amount of foaming material added in step S3 is 19 parts by weight.
[0062] Comparative Example 2
[0063] An inorganic grouting material, whose components and preparation method are basically the same as those of Example 1, except that in step S3, no foaming material is added and the amount thereof is 0.
[0064] Performance test: The samples obtained in Example 1, Example 4, Example 5, and Comparative Example 2 were tested for tensile bond strength with cement mortar, tensile bond strength with insulation board, and slip according to the method described in T / CECS 574-2019 "Technical Code for External Insulation Renovation of Exterior Walls of Existing Buildings"; and their density was tested according to the method described in GB / T 5486-2008 "Test Methods for Inorganic Rigid Insulation Products". The test results are shown in Table 2.
[0065] Table 2 Performance test of different amounts of foaming materials in Example 1, Example 4, Example 5 and Comparative Example 2
[0066] Test items Example 1 Example 4 Example 5 Comparative Example 2 Foaming material dosage / part 15 10 19 0 Tensile bond strength with cement mortar / MPa 1.33 1.41 0.95 1.55 Tensile bonding strength with insulation board / MPa 0.61 0.68 0.38 0.8 Slip / mm 0.2 0.2 0.5 0.1 <![CDATA[Density / kg / m 3 > 1352 1571 1153 1772
[0067] As can be seen from Table 2, in Example 1, Example 4, and Example 5, adjusting the amount of foaming material has an impact on the tensile bond strength, slip, and density of the grouting material. This is because the treated foaming material is more sensitive to microwaves, and can heat up and release the adsorbed CO2 gas under the action of microwaves, so that the grouting material can foam and fill the pores between the insulation layer and the concrete exterior wall. In Example 4, the amount of foaming material is reduced to 10 parts by weight, and the gas content of the grouting material is reduced after foaming, and the corresponding tensile bond strength and density are improved. In contrast, in Example 5, the gas content is large after foaming, the tensile bond strength and density are reduced, and the slip is increased.
[0068] In comparative example 2, the amount of foaming material is 0, that is, the grouting material cannot be foamed, and its tensile bond strength and density are improved, and the slippage is reduced. However, the grouting material that cannot be foamed has a large weight and poor thermal insulation performance. It cannot fully fill the pores between the thermal insulation layer and the concrete outer wall during the grouting process, and it is difficult to perfectly treat the hollowing of the outer wall thermal insulation layer.
[0069] (III) Study on the effect of viscosity modifier dosage on the performance of inorganic grouting materials for in-situ reinforcement and repair
[0070] Example 6
[0071] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, the components and preparation method of which are substantially the same as those of Example 1, except that the amount of the viscosity improver (bentonite) added in step S2 is 2 parts by weight.
[0072] Example 7
[0073] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, the components and preparation method of which are substantially the same as those of Example 1, except that the amount of the viscosity improver (bentonite) added in step S2 is 3 parts by weight.
[0074] Comparative Example 3
[0075] An inorganic grouting material, whose components and preparation method are basically the same as those of Example 1, except that in step S2, no viscosity improver (bentonite) is added, and its amount is 0.
[0076] Performance test: The samples obtained in Example 1, Example 6, Example 7, and Comparative Example 3 were tested for tensile bond strength with cement mortar, tensile bond strength with insulation board, and slip according to the method described in T / CECS 574-2019 "Technical Code for External Insulation Renovation of Exterior Walls of Existing Buildings"; and their density was tested according to the method described in GB / T 5486-2008 "Test Methods for Inorganic Rigid Insulation Products". The test results are shown in Table 3.
[0077] Table 3 Performance test of different viscosity improver dosages in Example 1, Example 6, Example 7 and Comparative Example 3
[0078] Test items Example 1 Example 6 Example 7 Comparative Example 3 Viscosity improver (bentonite) dosage / part 2.5 2 3 0 Tensile bond strength with cement mortar / MPa 1.33 1.29 1.36 1.12 Tensile bonding strength with insulation board / MPa 0.61 0.58 0.65 0.45 Slip / mm 0.2 0.1 0.2 0.6 <![CDATA[Density / kg / m 3 > 1352 1246 1477 1151
[0079] As shown in Table 3, the adjustment of the amount of bentonite in Example 1, Example 6, and Example 7 has little effect on the tensile bond strength and slip of the grouting material, but has a more obvious effect on the density. This is because bentonite can absorb excess free water in the grouting material, adjust the viscosity of the slurry, and thus affect the slurry foaming process. In Example 6, the amount of bentonite is reduced, the viscosity of the slurry decreases, and the slurry has a larger gas content and a smaller density after foaming. Example 7 is the opposite.
[0080] In comparative example 3, the amount of bentonite used is 0, the viscosity of the grouting material is relatively low, the slippage is relatively large, and the tensile bond strength and density are relatively low. This makes it easy for the grouting material to slip and flow between the pores of the insulation layer and the concrete outer wall during the grouting construction process, making it difficult to ensure the construction quality.
[0081] (IV) Study on the effect of microwave treatment on the performance of inorganic grouting materials for in-situ reinforcement and repair
[0082] Example 8
[0083] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, wherein the components and preparation method thereof are substantially the same as those of Example 1, except that in step S4, the microwave frequency is 1000 MHz and the irradiation time is 5 min.
[0084] Example 9
[0085] An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, whose components and preparation method are substantially the same as those of Example 1, except that in step S4, the microwave frequency is 3000 MHz and the irradiation time is 8 min.
[0086] Comparative Example 4
[0087] An inorganic grouting material, whose components and preparation method are basically the same as those in Example 1, except that no microwave treatment is performed in step S4.
[0088] Performance test: The samples obtained in Example 1, Example 8, Example 9, and Comparative Example 4 were tested for tensile bond strength with cement mortar, tensile bond strength with insulation board, and slip according to the method described in T / CECS 574-2019 "Technical Code for External Insulation Renovation of Exterior Walls of Existing Buildings"; and their density was tested according to the method described in GB / T 5486-2008 "Test Methods for Inorganic Rigid Insulation Products". The test results are shown in Table 4.
[0089] Table 4 Performance test of different microwave treatment processes in Example 1, Example 8, Example 9 and Comparative Example 4
[0090] Test items Example 1 Example 8 Example 9 Comparative Example 4 Microwave frequency / MHz 2000 1000 3000 / Irradiation time / min 6 5 8 / Tensile bond strength with cement mortar / MPa 1.33 1.46 1.03 1.57 Tensile bonding strength with insulation board / MPa 0.61 0.73 0.44 0.85 Slip / mm 0.2 0.2 0.5 0.1 <![CDATA[Density / kg / m 3 > 1352 1602 1220 1819
[0091] As can be seen from Table 4, adjusting the microwave treatment process in Example 1, Example 8, and Example 9 has a relatively obvious effect on the tensile bond strength, slip, and density of the grouting material. This is because the microwave treatment affects the foaming process of the grouting material. In Example 8, the microwave frequency is low and the time is short, so the foaming is insufficient, the slurry has a small gas content, and the tensile bond strength and density are increased; in Example 9, the microwave frequency is high and the time is long, so the foaming is more sufficient, the slurry has a large gas content, the tensile bond strength and density are reduced, and at the same time, the internal cohesion of the slurry with a large gas content decreases, which increases the slip.
[0092] In Comparative Example 4, when the microwave treatment process is not used, the grouting material cannot be foamed, the slurry density is large, the tensile bond strength after hardening is relatively large, and the slippage is small. However, this makes the grouting material have poor thermal insulation performance, making it difficult to fill the pores between the insulation layer and the concrete outer wall, and it is difficult to ensure the construction quality.
[0093] The inorganic grouting material for in-situ reinforcement and repair of the exterior wall insulation layer provided by the present invention can meet the performance requirements for inorganic grouting materials in T / CECS574-2019 "Technical Code for External Insulation Renovation of Exterior Walls of Existing Buildings". The foaming process can also enable it to fully fill the pores and have good thermal insulation properties. At the same time, it can also play a role in solidifying CO2 and has good social and environmental benefits.
[0094] The above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the protection scope of the present invention. Those skilled in the art can modify or replace the technical solution of the present invention according to the idea of the present invention without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer, characterized in that: The inorganic grouting material is mainly made of the following raw materials in parts by weight: 24 to 56 parts of vacuum aluminothermic reduction lithium slag powder, 10 to 30 parts of siliceous admixture, 10 to 20 parts of foaming material, 2 to 5 parts of active stimulant, 2 to 4 parts of viscosity improver, 1 to 2 parts of foam stabilizer, 0.5 to 1.5 parts of surfactant, and 13.5 to 18.5 parts of water.
2. The inorganic grouting material for in-situ reinforcement and repair of the exterior wall insulation layer according to claim 1, characterized in that: The foaming material is prepared by the following method: one or more of waste rubber, waste asphalt waterproofing membrane, and waste plastic are carbonized into porous carbon materials and then immersed in an impregnation liquid, and then the impregnated porous carbon materials are placed in a critical CO2 environment to fully adsorb CO2, thereby obtaining the foaming material; the impregnation liquid is one or more of ethanolamine, ethylenediamine, and tetraethylenepentamine.
3. The inorganic grouting material for in-situ reinforcement and repair of exterior wall insulation layer according to claim 1, characterized in that: The vacuum aluminothermic reduction lithium slag powder is the reduction slag produced by the vacuum aluminothermic reduction method to prepare metallic lithium, and the average particle size of the vacuum aluminothermic reduction lithium slag powder is not greater than 100 μm.
4. The inorganic grouting material for in-situ reinforcement and repair of exterior wall insulation layer according to claim 1, characterized in that: The siliceous admixture is one or more of organic silicon waste residue, ultrafine fly ash, and silica ash, and the average particle size of the siliceous admixture is not greater than 10 μm.
5. The inorganic grouting material for in-situ reinforcement and repair of exterior wall insulation layer according to claim 1, characterized in that: The active stimulant is an alkaline solution, and the alkaline solution is at least one of NaOH, Na2CO3, Na2SiO3, and KOH.
6. The inorganic grouting material for in-situ reinforcement and repair of exterior wall insulation layer according to claim 1, characterized in that: The viscosity modifier is at least one of bentonite, attapulgite and diatomaceous earth.
7. The inorganic grouting material for in-situ reinforcement and repair of exterior wall insulation layer according to claim 1, characterized in that: The foam stabilizer is at least one of redispersible latex powder, hydroxypropyl methylcellulose and xanthan gum.
8. The inorganic grouting material for in-situ reinforcement and repair of exterior wall insulation layer according to claim 1, characterized in that: The surfactant is polycarboxylate sodium salt.
9. A method for preparing an inorganic grouting material for in-situ reinforcement and repair of an exterior wall insulation layer according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: Add active stimulant, foam stabilizer and surfactant into water in sequence and mix evenly to obtain a mixed solution; S2: mixing the vacuum aluminothermic reduction lithium slag powder, the siliceous admixture and the viscosity improver uniformly to obtain a mixture; S3: adding the mixture obtained in S2 and the foaming material to the mixed solution obtained in S1 in sequence, and stirring evenly to obtain a slurry; S4: When in use, the slurry obtained in S3 is injected into the part of the exterior wall insulation layer that needs to be repaired and reinforced, and then the repair part is irradiated with 1000MHz to 3000MHz microwaves for 5 to 8 minutes to obtain the inorganic grouting material for in-situ reinforcement and repair of the exterior wall insulation layer.